Pengaruh Komunikasi, Insentif Dan Pengembangan Karir Terhadap Kinerja Karyawan PT Bersama Era Sentosa Tama - Ainul Diniah; Eko Budi Satoto; Nursaidah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2025)
Human Resource Management (HRM) is a crucial part of a modern organization, as a company's success depends heavily on the quality and management of its human resources. Therefore, improving employee performance through planned, directed, and sustainable HRM management is crucial for a company to survive and thrive amidst increasingly fierce competition. This study aims to analyze the influence of three aspects: communication, incentives, and career development on employee performance at PT Bersama Era Sentosa Tama. The approach used in this study is quantitative, with a survey method using questionnaires administered to all 200 employees. The data obtained were analyzed using multiple linear regression with the help of SPSS. The results show that communication has a negative and significant effect on employee performance, while incentives and career development have a positive and significant effect. The adjusted R Square value of 27.8% indicates that the three independent variables together are able to explain variations in employee performance, while the remainder is influenced by other factors not included in this research model. These findings confirm that improving internal communication, adjusting performance-based incentive systems, and strengthening career development programs are important strategies in improving employee performance sustainably.